RACK STORAGE COMPONENT DESIGN BY PARAMETRIC CURVES AND SURFACES - Puji Astuti; Kusno Kusno (Jurnal ILMU DASAR, 2012)
The purpose of study is to obtain procedures of designing several models of rack support and pole component, so that the shape are varies, symmetrical, graded, and balance. The results show that the procedure of designing rack support component can be done by taking some data of a space frame construction of the cube, triangular prism, or cone, then we set a few points on the frame to build piece of parametric curve. Finally we interpolate the curves to find a rack support surfaces. As for the rack pole component, the procedures are: we extract data of straight line segments, oblique or helical shape, then we enumerate the lines into several sub-segments, and then breaks it down to build the trending, chain, and graded curve to get a balance rack pole .